Detection of extended spectrum beta-lactamases and resistance in members of the Enterobacteriaceae family isolated from healthy sheep and dogs in Umuarama, Paraná, Brazil - Oliveira, Patricia Alves de (2016)
Bacterial resistance is a primary public health concern worldwide. Within this context, pets and breeding animals act as reservoirs for multidrug-resistant bacteria (MR), such as those producing extended spectrum beta-lactamases (ESBL) and those presenting plasmid-mediated quinolone resistance (PMQR). The aim of this study was to detect the presence of ESBL and PMQR in members of the Enterobacteriaceae family, isolated from healthy sheep and dogs from non-intense farming rural properties in the Umuarama region of Paraná, Brazil. A total of 81 oral and rectal swabs from dogs and sheep from 11 small rural properties were analyzed. These swabs were inoculated in tubes containing brain heart infusion broth (BHI), and the resulting cultures were inoculated on MacConkey agar (MAC) supplemented with 10 ?g/mL cefotaxime for the selection of ESBL producers. The cells were also plated on MAC supplemented with 50 ?g/mL nalidixic acid for selecting quinolone-resistant enterobacteria. The bacterial isolates were subjected to biochemical identification tests, antibiograms, double-disk synergic tests, and polymerase chain reaction analysis for resistance-inducing genes (blaESBL, qnr, and genes encoding efflux pump and acetylases). Four (5.00%) bacterial isolates (3 Escherichia coli and 1 Morganella morganii) resistant to cephalosporins and/or quinolones were identified; of these, three (75%) isolates were from sheep and one (25%) from a dog. These findings indicate the presence of MR bacteria in the normal microbiota of the animals studied. Animals colonized with such bacteria can contribute to the dissemination of antimicrobial resistance to other animals, environment, and/or human beings and can harbor endogenous infections in unfavorable conditions, which have poor prognosis due to the limited therapeutic options.